2021
DOI: 10.3389/fgene.2021.743738
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IGF2BP3 as an Adverse Prognostic Biomarker of Gliomas

Abstract: N6-methyladenosine (m6A) RNA modification can alter gene expression and function by regulating RNA splicing, stability, translocation, and translation. It is involved in various types of cancer. However, its role in gliomas is not well known. This study aimed to determine the prognostic value of the m6A RNA methylation regulator in gliomas and investigate the underlying mechanisms of the aberrant expression of m6A-related genes.mRNA expression profiles and clinical information of 448 glioma samples were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Similarly, SRSF7 can specifically regulate m6A of mRNA of PDZ binding kinase (PBK) to promote its AS response regulated by insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), which ultimately leads to GBM proliferation and migration [ 97 ]. IGF2BP3 has also been shown to be a biomarker for gliomas [ 98 ]. Probable ATP-dependent RNA helicase DDX46, involved in pre-mRNA splicing and upregulated in GBM, promotes cell proliferation by activating MAPK-p38 signaling [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SRSF7 can specifically regulate m6A of mRNA of PDZ binding kinase (PBK) to promote its AS response regulated by insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), which ultimately leads to GBM proliferation and migration [ 97 ]. IGF2BP3 has also been shown to be a biomarker for gliomas [ 98 ]. Probable ATP-dependent RNA helicase DDX46, involved in pre-mRNA splicing and upregulated in GBM, promotes cell proliferation by activating MAPK-p38 signaling [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 IMPs play its role in post‐translational RNA processing, such as transcript localization, translation and stabilization 31 , 32 , 33 ; additionally, IMPs family were recently identified as a family of m6A readers. 8 , 34 However, previous research mainly focussed on the biological functions of IMPs in tumours and embryogenesis. For example, IMP3 participates in RNA trafficking and stabilization which promotes cell proliferation, migration in tumour progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…IMP3, also known as insulin‐like growth factor 2 (IGF2) mRNA‐binding protein 3 (IGF2BP3), is a member of the insulin‐like growth factor 2 mRNA‐binding proteins family 28–30 . IMPs play its role in post‐translational RNA processing, such as transcript localization, translation and stabilization 31–33 ; additionally, IMPs family were recently identified as a family of m6A readers 8,34 . However, previous research mainly focussed on the biological functions of IMPs in tumours and embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP2 interacts with the CASC9/IGF2BP2 complex and accelerates aerobic glycolysis in GBM by regulating the mRNA of HK2. It was reported that high expression of IGF2BP3 in patients with glioma significantly reduced survival time, which was also associated with poor prognosis, suggesting that IGF2BP3 might be used as a potential prognostic biomarker for gliomas ( Liu et al, 2021b ; Sun et al, 2021 ; Xiong et al, 2022 ). The important role of modified m 6 A-related proteins in GBM provides new insights into the prognosis and treatment of GBM.…”
Section: A Methylation In Neurological Disordersmentioning
confidence: 99%